Moderating Effect of Job Satisfaction in the Relationship Between Nursing Work Environment and Turnover Intention: A Perspective From Magnet Hospitals in South Korea - Wonji Lee; Soyoung Yu (SAGE Open)
This study aimed to examine the mediating effect of job satisfaction on the impact of the nursing work environment on nurses’ turnover intention from the perspective of Magnet hospitals. Hospitals with Magnet accreditation have high nurse satisfaction, low nurse turnover, low vacancy rates, improved clinical outcomes, and enhanced patient satisfaction. A cross-sectional survey was conducted with 432 nurses working in 6 hospitals, including tertiary and general hospitals, in Seoul’s metropolitan area and Jeollabuk-do Province. The survey, conducted in 2023, used a self-administered questionnaire design and included items on the nursing work environment, job satisfaction, and turnover intention. The study utilized a 5-point Likert scale, revealing an average score of 3.02 for the nursing work environment, 3.18 for job satisfaction, and 3.42 for turnover intention. Significant differences in the nursing work environment, according to general characteristics, were identified in age ( p  < .001), education level ( p  = .027), desired department placement ( p  < .001), presence of treated illness ( p  < .001), and availability of desired rest days ( p  < .001). Additionally, the nursing work environment significantly influenced job satisfaction ( p  < .001). The Nursing Work Environment (β = .893, p  < .000) positively affects Job Satisfaction. Furthermore, Job Satisfaction (β = −.409, p  < .000) has a negative impact on Tourism Intention. Lastly, the Nursing Work Environment negatively influences Turnover Intention (β = −.288, p  = .003). Therefore, job satisfaction increases as the nursing work environment improves, leading to a decrease in turnover intention. The results emphasize the need to enhance the nursing work environment and job satisfaction to reduce nurses’ turnover intentions.